Influence of electrochemical active surface area on the oxygen evolution reaction and energy storage performance of MnO2‐multiwalled carbon nanotube composite. (20th May 2021) - Roy, Atanu; Ray, Apurba; Saha, Samik; Ghosh, Monalisa; Das, Trisha; Nandi, Mahasweta; Lal, Gobardhan; Das, Sachindranath
Summary: The current study emphasizes the influence of electrochemical active surface area (ECSA) on the electrochemical oxygen evolution reaction (OER) and supercapacitive performances of MnO2 ‐multiwalled carbon nanotube (MC) composites. The best sample exhibits an ECSA of 8.6 cm 2 . With the increase of ECSA both OER activity and the supercapacitive performance of the composites increases. The MC composite exhibits a low over potential (0.385 V) for OER activity. The composite displays outstanding catalytic activity for OER in the alkali medium as well as exhibits excellent supercapacitive activity (specific capacitance of 1039 F g −1 at a scan rate of 2 mV s −1 ). An asymmetric supercapacitor has also been developed which shows very high specific capacitance within a wide working potential of 1.8 V. This device can supply an energy and power density of 60.55 Wh kg −1 and 8.45 kW kg −1, respectively. The role of ECSA has been investigated in both oxygen evolution and supercapacitive process showing the promise of this multifunctional MnO2 ‐MWCNT composite for both energy storage but also in conversion. Abstract : This research work investigates the role of electrochemical active surface area (ECSA) on electrochemical oxygen evolution reaction (OER) and supercapacitive performance of MnO2 ‐multiwalled carbon nanotube (MC) based electrode material where both the performances increase with increase of ECSA. The composite exhibits a low overpotential of 385 mV in 1 M KOH electrolyte and also exhibits a specific capacitance of 1039 F g −1 in neutral Na2 SO4 electrolyte. This MC composite is an excellent material for multifunctional application.